Equilibrium Selection in Bargaining Models. - Binmore, K; Samuelson, L; Young, P (2003)
This paper examines evolutionary equilibrium selection in bargaining models. We show that random best-response and continuous best-response learning dynamics give rise to (different) simple sufficient conditions for identifying outcomes as stochastically stable. This allows us to characterize the implications of these dynamics in simple bargaining games.